2016
DOI: 10.1007/s00592-016-0879-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity amputation rates in people with diabetes as an indicator of health systems performance. A critical appraisal of the data collection 2000–2011 by the Organization for Economic Cooperation and Development (OECD)

Abstract: AimsCritical appraisal of secondary data made available by the OECD for the time frame 2000–2011.MethodsComparison of trends and variation of amputations in people with diabetes across OECD countries. Generalized estimating equations to test the statistical significance of the annual change adjusting for major potential confounders.ResultsA total of 26 OECD countries contributed to the OECD data collection for at least 1 year in the reference time frame, showing a decline in rates of over 40 %, from a mean of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 18 publications
3
54
1
2
Order By: Relevance
“…Data from national audits in many countries and the Organization for Economic Cooperation and Development (OECD) have demonstrated a signi cant reduction in the incidence of diabetes-related major LEA over years owing to diabetic foot ulcer prevention and care programs [9][10][11][12]. Nevertheless, studies have reported up to a 20-fold variation in the rate of major LEA among countries [13,14]. Furthermore, as per OECD estimates of 2017, Austria had a high agesex standardized rate of major LEA (13.20 per 100,000 population) in individuals with diabetes amongst European Countries [10].…”
mentioning
confidence: 99%
“…Data from national audits in many countries and the Organization for Economic Cooperation and Development (OECD) have demonstrated a signi cant reduction in the incidence of diabetes-related major LEA over years owing to diabetic foot ulcer prevention and care programs [9][10][11][12]. Nevertheless, studies have reported up to a 20-fold variation in the rate of major LEA among countries [13,14]. Furthermore, as per OECD estimates of 2017, Austria had a high agesex standardized rate of major LEA (13.20 per 100,000 population) in individuals with diabetes amongst European Countries [10].…”
mentioning
confidence: 99%
“…infrequency of this event. A recent study of 26 Organization for Economic Cooperation and Development countries found a median rate of 7.8 events/100,000 people with diabetes (2). A review of global variation in incidence that mainly included European countries and the U.S. found annual incidence ranging from 4.6 to 960/10,000 people with diabetes, but 85% of countries/states examined had an annual incidence ,100/10,000 (3).…”
mentioning
confidence: 99%
“…населения по сравнению с данными Венгрии, где этот показатель составил 1,1 на 100 тыс. населения [10]. Данная вариабельность может объясняться рядом при-чин, в том числе различными способами кодирования медицинских услуг, существенными различиями в распро-страненности СД, различным уровнем оказания специа-лизированной медицинской помощи, а также качеством сбора информации.…”
Section: Discussionunclassified